Diseño e implementación de un sistema de medición y cuantificación de emisiones de carbono en los invernaderos de tomates riñón en la plantación “Toapanta Oswaldo” ubicada en Huapante Grande de la provincia de Tungurahua. - Quishpe Tigasi, Rene Javier (2022)
The objective of this technological proposal is the implementation of an electronic device that identifies and quantifies gases derived from carbon such as Carbon Dioxide, Methane and Nitrous Oxide, defining the importance of gas analysis to determine risk levels when entering or staying for a certain time in the place of study, the field analysis conducted focuses on the greenhouse of kidney tomatoes in the plantation "Toapanta Oswaldo" located in Huapante Grande of the canton Santiago de Píllaro, province of Tungurahua. Under these parameters the electronic device was designed and implemented under quantitative and experimental methodology that determines the technical specifications, the device has a microcontroller, sensors categorized as electrochemical duly calibrated with mathematical processes, computational, verification at zero level and by a reference standard, with the possibility of being visualized through an LCD type screen and with an App designed in a software developer environment for Android operating system, which is linked through wireless communication protocols, it also has the ability to issue visual alarm messages at the time of exceeding hazardous values of each of the gases, it has a data storage and the system is protected by a frame which prevents any corrosion caused by the greenhouse environment. With the implementation of the electronic device, it was determined according to the analyses carried out in the greenhouse that CO2 is predominant with its presence, since in each analysis it presented average values of 366.1 ppm. It should be emphasized that the presence of the greenhouse gas is produced by human respiration and the typical atmospheric concentration is 350 to 450 ppm, while CH4 and N2O presented quite low concentration values of 0.09 and 0.10 ppm, respectively. Accordingly, it is determined that these are acceptable air quality values.